A method for preparing a composite coating of carbon fiber thermal insulation material
By purifying carbon fibers, doping composite metal elements and carbon coating on the surface, combined with the technical means of Al2O3-TiO2 coating, the existing insulation coating has solved the problems of high thermal conductivity, insufficient wear resistance and adhesion ability in high temperature environments, and achieved efficient insulation performance and wear resistance.
Patent Information
- Application Number
- CN202311627530.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-11-30
AI Technical Summary
The existing thermal insulation coating has a high thermal conductivity under high temperature environments, and its wear resistance and adhesion capabilities are insufficient, making it difficult to meet the needs of complex thermal protection systems.
By purifying the carbon fiber and doping the composite metal elements on the surface, the surface carbon coating is carried out using a high-temperature furnace to form an amorphous carbon structure, and the thermal insulation performance and adhesion of the carbon fiber are improved by the Al2O3-TiO2 coating layer.
It significantly improves the thermal insulation performance, wear resistance and adhesion of the coating, provides extremely high thermal insulation capabilities, and is suitable for various thermal protection systems.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon fiber thermal insulation material composite coating. Background Art
[0002] The country's development in new energy, semiconductors, machinery, automobiles, railways, etc. has driven the development of corresponding coating technologies. The coating can effectively resist external erosion and extend their service life.
[0003] Thermal insulation coating combines the characteristics of both coating and thermal insulation material. It is a kind of fiber-thick paste coating that can reduce heat loss. It is applied to the surface of the material object that needs to be insulated, and after it dries, it forms a thermal insulation layer with a certain strength. The thermal insulation layer formed by thermal insulation coating has low thermal conductivity and significant thermal insulation effect. It is widely used in semiconductors, high-temperature equipment, high-temperature thermal fields, etc. Summary of the invention
[0004] The present invention provides a method for preparing a composite coating of a carbon fiber thermal insulation material, the method comprising: purifying the carbon fiber, then doping the surface with a composite metal element, placing the doped carbon fiber in a high-temperature furnace for surface carbon coating, cracking the organic carbon source on the surface of the carbon fiber under the catalytic action of the composite metal element to form amorphous carbon, then performing surface modification to obtain surface-modified carbon fiber, and then stirring and mixing with the components in the coating, applying, and obtaining a composite coating of a thermal insulation material containing carbon fiber. The carbon fiber of the present invention has good performance, and through the catalysis of the composite metal during the pyrolysis process, amorphous carbon with a porous structure is formed on the surface, which has good thermal insulation ability. The coating of the present invention has extremely high thermal insulation ability, corrosion resistance, wear resistance and adhesion ability, and can be used for thermal insulation coatings in various thermal protection systems.
[0005] A method for preparing a carbon fiber thermal insulation material composite coating, characterized in that the specific preparation steps include:
[0006] 1) adding carbon fiber into a heating furnace, introducing a purifying agent, and heating and purifying in a sealed manner for a predetermined time to obtain purified carbon fiber;
[0007] 2) dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction for a predetermined time to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0008] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, introducing acetylene or ethylene, heating and carbon deposition, and obtaining carbon fiber with surface carbon coating;
[0009] 4) immersing the carbon fiber in step 3 in a concentrated nitric acid solution for surface activation;
[0010] 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and then conducting a closed hydrothermal reaction for a predetermined time to obtain Al2O3-TiO2 coated carbon fiber;
[0011] 6) 20-25 parts of the carbon fiber obtained in step 5), 40-45 parts of phenolic resin, 12-15 parts of styrene / methyl methacrylate copolymer, 5503-5 parts of silane coupling agent, and 20-25 parts of organic solvent are mixed uniformly to obtain a coating;
[0012] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0013] Furthermore, step 1) is to add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat and purify at 800-1000° C. for 4-5 hours; cool naturally to room temperature, and take out.
[0014] Furthermore, in step 2), the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100 g: x mmol: 2x mmol, wherein x is 1-2; and the reaction is carried out in a closed hydrothermal reaction at 60-70° C. for 6-8 hours.
[0015] Furthermore, the step 3) is heated to 360-400° C., acetylene or ethylene is introduced, and carbon deposition is performed for 4-6 hours.
[0016] Furthermore, step 4) is as follows: immersing the carbon fiber in a nitric acid solution and heating it to 50-70° C. for 20-30 minutes, taking it out and washing it with deionized water, and drying it.
[0017] Furthermore, step 5) is to uniformly disperse butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2-3:4-6, and then add the carbon fiber obtained in step 4, add ethanol in an amount equal to that of water, and then carry out a closed hydrothermal reaction at 70-80°C for more than 4 hours to obtain Al2O3-TiO2 coated carbon fiber.
[0018] Furthermore, a thermal insulation composite coating containing carbon fiber material is provided, and the carbon fiber thermal insulation composite coating is prepared by the method described.
[0019] Beneficial technical effects of the present invention
[0020] 1) The carbon fiber is purified before modification to reduce the content of heteroatomic metal ions in the carbon fiber. In an environment containing glycerol, yttrium and calcium elements can be precipitated on the surface of the carbon fiber to obtain yttrium oxide and calcium oxide with high specific surface area. The yttrium oxide and calcium oxide work together to improve the effect of amorphous carbon deposition on the surface of carbon nanotubes, thereby increasing the Al 2 O3 -TiO 2 Uniformity of coating;
[0021] 2) After coating, the surface is treated with concentrated nitric acid to avoid defects in the carbon fiber. At the same time, yttrium oxide and calcium oxide can be dissolved during the surface treatment, so that the carbon on the surface of the carbon fiber presents a porous structure, thereby further improving the Al 2 O 3 -TiO 2 The bonding degree between the coating layer and the carbon fiber increases the Al 2 O 3 -TiO 2 Wrapping effect;
[0022] 3) Al 2 O 3 -TiO 2 Evenly coating the surface of carbon fiber can improve the thermal insulation performance of carbon fiber. DETAILED DESCRIPTION
[0023] The present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples within the scope not exceeding the gist of the present invention.
[0024] Example 1
[0025] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 800° C. for purification for 5 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0026] 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, wherein the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100 g: 1 mmol: 2 mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 60° C. for 8 hours to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0027] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 360° C., introducing acetylene, and carbon deposition for 6 hours to obtain carbon-coated carbon fiber;
[0028] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 50°C for 30min, then taken out and washed with deionized water for 3 times and dried;
[0029] 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2:4, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and reacting at 70° C. for 4 hours in a closed hydrothermal reaction to obtain Al2O3-TiO2 coated carbon fiber;
[0030] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0031] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0032] Example 2
[0033] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 1000° C. for purification for 4 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0034] 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, wherein the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100 g: 2 mmol: 4 mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 70° C. for 6 hours to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0035] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 400° C., introducing acetylene, and carbon deposition for 4 hours to obtain carbon-coated carbon fiber;
[0036] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 70°C for 20min, then taken out and washed with deionized water for 3 times and dried;
[0037] 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:3:6, and then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and then performing a closed hydrothermal reaction at 70° C. for 4 hours to obtain Al2O3-TiO2 coated carbon fiber;
[0038] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0039] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0040] Example 3
[0041] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 900° C. for purification for 5 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0042] 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100g:1.5mmol:3mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 70°C for 8 hours to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0043] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 380° C., introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0044] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0045] 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2.5:5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and reacting at 75° C. for 4 hours in a closed hydrothermal reaction to obtain Al2O3-TiO2 coated carbon fiber;
[0046] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0047] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0048] Comparative Example 1
[0049] 1) The carbon fiber was immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0050] 2) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2.5:5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and then performing a closed hydrothermal reaction at 75° C. for 4 hours to obtain Al2O3-TiO2 coated carbon fiber;
[0051] 3) 25 parts of carbon fiber, 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent were mixed uniformly to obtain a coating;
[0052] 4) coating the coating on the surface of the substrate and drying it to obtain the thermal insulation composite coating containing the carbon fiber material.
[0053] Comparative Example 2
[0054] 1) placing the carbon fiber in a closed tubular heating furnace, heating it to 380°C, introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0055] 2) The carbon fibers were immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0056] 3) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2.5:5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and reacting at 75° C. for 4 hours in a closed hydrothermal reaction to obtain Al2O3-TiO2 coated carbon fiber;
[0057] 4) 25 parts of the carbon fiber, 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent were mixed to obtain a coating;
[0058] 5) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0059] Comparative Example 3
[0060] 1) dispersing carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, wherein the ratio of carbon fiber to yttrium nitrate and calcium nitrate is 100 g:1.5 mmol:3 mmol; adding ammonia water after mixing evenly, conducting a closed hydrothermal reaction at 70° C. for 8 hours, and forming yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0061] 2) placing the carbon fiber in a closed tubular heating furnace, heating to 380°C, introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0062] 3) The carbon fiber was immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0063] 4) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2.5:5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and then performing a closed hydrothermal reaction at 75° C. for 4 hours to obtain Al2O3-TiO2 coated carbon fiber;
[0064] 5) 25 parts of carbon fiber, 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent were mixed uniformly to obtain a coating;
[0065] 6) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0066] Comparative Example 4
[0067] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 900° C. for purification for 5 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0068] 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate aqueous solution, the ratio of the carbon fiber to yttrium nitrate is 100g:1.5mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 70°C for 8 hours to form yttrium oxide in situ on the surface of the carbon fiber;
[0069] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 380° C., introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0070] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0071] 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2.5:5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and reacting at 75° C. for 4 hours in a closed hydrothermal reaction to obtain Al2O3-TiO2 coated carbon fiber;
[0072] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0073] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0074] Comparative Example 5
[0075] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 900° C. for purification for 5 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0076] 2) Dispersing the purified carbon fiber in glycerol, adding calcium nitrate aqueous solution, the ratio of the carbon fiber to calcium nitrate is 100g:3mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 70°C for 8 hours to form calcium oxide in situ on the surface of the carbon fiber;
[0077] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 380° C., introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0078] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0079] 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2.5:5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and reacting at 75° C. for 4 hours in a closed hydrothermal reaction to obtain Al2O3-TiO2 coated carbon fiber;
[0080] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0081] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0082] Comparative Example 6
[0083] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 900° C. for purification for 5 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0084] 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100g:1.5mmol:3mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 70°C for 8 hours to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0085] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 380° C., introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0086] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0087] 5) uniformly dispersing butyl titanate in deionized water, wherein the molar ratio of butyl titanate to water is 1:2.5, then adding the carbon fiber obtained in step 4, adding ethanol in an amount equal to that of water, and then performing a closed hydrothermal reaction at 75° C. for 4 hours to obtain TiO2-coated carbon fiber;
[0088] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0089] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0090] Comparative Example 7
[0091] 1) Add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat at 900° C. for purification for 5 hours; cool naturally to room temperature, take out, and obtain purified carbon fiber;
[0092] 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100g:1.5mmol:3mmol; adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction at 70°C for 8 hours to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber;
[0093] 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, heating to 380° C., introducing acetylene, and carbon deposition for 5 hours to obtain carbon-coated carbon fiber;
[0094] 4) The carbon fiber in step 3 is immersed in a 40wt% concentrated nitric acid solution and heated to 60°C for 25min, then taken out and washed with deionized water for 3 times and dried;
[0095] 5) Aluminum nitrate is uniformly dispersed in deionized water, wherein the molar ratio of aluminum nitrate to water is 1:5, and then the carbon fiber obtained in step 4 is added, and ethanol equal to the amount of water is added, and then a closed hydrothermal reaction is carried out at 75° C. for 4 hours to obtain Al2O3-coated carbon fiber;
[0096] 6) taking 25 parts of carbon fiber obtained in step 5), 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent and mixing them uniformly to obtain a coating;
[0097] 7) coating the coating on the surface of the substrate and drying to obtain the thermal insulation composite coating containing the carbon fiber material.
[0098] Comparative Example 8
[0099] 1) 25 parts of carbon fiber, 40 parts of phenolic resin, 12 parts of styrene / methyl methacrylate copolymer, 5503 parts of silane coupling agent and 25 parts of organic solvent were mixed uniformly to obtain a coating;
[0100] 2) coating the coating on the surface of the substrate and drying it to obtain the thermal insulation composite coating containing the carbon fiber material.
[0101] Experiments and Data
[0102] The material properties of the material of the present invention are tested under the following test conditions.
[0103] Thermal conductivity
[0104] Take a coating sample with a size of 80 mm × 80 mm, cool it to room temperature, and place it in an intelligent double-plate thermal conductivity tester to test the thermal conductivity of the sample.
[0105] Wear resistance test
[0106] The test method refers to the standard GB / T23988 "Sandfalling Method for Determination of Abrasion Resistance of Coatings": the sample is placed in an environment of 25°C and 50% humidity for 24 hours in advance, and then tested. Standard sand is dropped from a height of 914mm onto the sample at a 45° angle. The amount of sandfall is calculated based on the wear area, and the wear resistance of the sample to be tested is calculated according to the formula: A=V / T, where: A is wear resistance, in liters per micron (L / μm), V is the amount of abrasive used, in liters L, and T is the coating thickness, in μm;
[0107] The test results of the embodiments and comparative examples are shown in Table 1 below. It can be seen from comparative examples 1-3 that the purification of the carbon fiber surface, catalyst deposition and carbon coating treatment significantly affect the thermal conductivity and wear resistance of the material, and the synergistic effect of yttrium oxide and calcium oxide can improve the wear resistance and reduce the thermal conductivity, while the composite coating of aluminum oxide and titanium dioxide mainly affects the wear resistance of the material. The present invention greatly improves the wear resistance of the material and reduces the thermal conductivity by purifying the carbon fiber, catalytic carbon coating, and composite coating of oxides, thereby obtaining a wear-resistant and thermal insulation coating.
[0108] Table 1
[0109] <![CDATA[Thermal conductivity (*10 -2 W / m·k)]]> Wear resistance (L / μm) Example 1 36.0 5.62 Example 2 35.6 5.75 Example 3 35.8 5.79 Comparative Example 1 55.6 4.05 Comparative Example 2 52.5 4.30 Comparative Example 3 45.8 4.55 Comparative Example 4 40.7 5.10 Comparative Example 5 39.6 5.25 Comparative Example 6 36.8 4.90 Comparative Example 7 37.9 5.15 Comparative Example 8 64.5 3.56
[0110] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for preparing a carbon fiber thermal insulation material composite coating, characterized in that: The specific preparation steps include: 1) Add carbon fiber into a heating furnace, introduce a purifying agent, and heat and purify in a sealed manner for a predetermined time to obtain purified carbon fiber; 2) Dispersing the purified carbon fiber in glycerol, adding yttrium nitrate and calcium nitrate aqueous solution, adding ammonia water after mixing evenly, and conducting a closed hydrothermal reaction for a predetermined time to form yttrium oxide and calcium oxide in situ on the surface of the carbon fiber; 3) placing the carbon fiber obtained in step 2) in a closed tubular heating furnace, introducing acetylene or ethylene, heating and carbon deposition, and obtaining carbon fiber coated with surface carbon; 4) immersing the carbon fiber in step 3) in a concentrated nitric acid solution for surface activation; 5) uniformly dispersing butyl titanate and aluminum nitrate in deionized water, then adding the carbon fiber obtained in step 4), adding ethanol in an amount equal to that of water, and then conducting a closed hydrothermal reaction for a predetermined time to obtain Al2O3-TiO2 coated carbon fiber; 6) 20-25 parts of the carbon fiber obtained in step 5), 40-45 parts of phenolic resin, 12-15 parts of styrene / methyl methacrylate copolymer, 3-5 parts of silane coupling agent 550, and 20-25 parts of organic solvent are mixed uniformly to obtain a coating; 7) The coating is applied on the surface of the substrate and dried to obtain a thermal insulation composite coating containing carbon fiber material.
2. The method according to claim 1, characterized in that The step 1) is to add the carbon fiber into a closed heating furnace, introduce methyl chloride, and heat and purify at 800-1000° C. for 4-5 hours; cool naturally to room temperature, and take out.
3. The method according to claim 1, characterized in that In step 2), the ratio of the carbon fiber to yttrium nitrate and calcium nitrate is 100 g: x mmol: 2x mmol, wherein x is 1-2; and the reaction is carried out in a closed hydrothermal reaction at 60-70° C. for 6-8 hours.
4. The method according to claim 1, characterized in that In step 3), heat to 360-400°C, introduce acetylene or ethylene, and perform carbon deposition for 4-6 hours.
5. The method according to claim 1, characterized in that Step 4) is as follows: immersing the carbon fiber in a nitric acid solution and heating it to 50-70° C. for 20-30 minutes, taking it out and washing it with deionized water, and drying it.
6. The method according to claim 1, characterized in that Wherein step 5) is to uniformly disperse butyl titanate and aluminum nitrate in deionized water, wherein the molar ratio of butyl titanate, aluminum nitrate and water is 1:2-3:4-6, and then add the carbon fiber obtained in step 4, add ethanol in an amount equal to that of water, and then carry out a closed hydrothermal reaction at 70-80°C for more than 4 hours to obtain Al2O3-TiO2 coated carbon fiber.
7. A carbon fiber thermal insulation material composite coating, characterized in that: The carbon fiber thermal insulation composite coating is prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Antioxidant ablation-resistant coating and preparation method thereof
CN115851070A
Preparation method of composite carbon fiber thermal insulation material
CN116986887A
Cited By
Coating for high-performance light-weight carbon fiber and preparation method thereof
CN121110376A
A coating for high-performance lightweight carbon fibers and a method for producing the same
CN121110376B